The Impacts of Scaffolding on Metacognition and Students’ Ability of Essays Writing - Budiyono, Herman; Eriyani, Elfa; Harjono, Hary Soedarto; Pudjaningsih, Wiwik (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to examine and describe the effect of scaffolding on the metacognition of writing knowledge and the students’ ability to write essays. The research design used was quasi-experiment with pretest and posttest designs. The independent variable of this study was scaffolding learning and the dependent variables were the metacognition of writing knowledge and the students’ ability to write essays. The research sample consisted of two groups, which were the experimental class and the control class. The results showed that in general scaffolding writing learning (1) had a significant negative effect on metacognition of writing knowledge of students (sig. 0.012) and (2) significantly positive effect on students’ ability of essays writing (0.001). Implications and future research are also discussed.